اختلاف أسانيدالحديث النبوي وأثره في اختلاف الفقهاء - حمدي, نورة (University of Eloued-جامعة الوادي, 2016)
تطرقت في ىذا البحث اختلاف أسانيد الحديث النبوي وأثره في اختلاف الفقياء، فارتأيت في تقسيم بحثي إلى ثلاثة فصول تناولت في الفصل الأول توضيح أسباب الاختلاف في الأسانيد والذي يتمثل في الوىم والخطأ وسلوك الجادة والقلب والإد ا رج وغيرىا. وأمّا الثاني فإني تحدثت فيو عن الاختلاف في الأسانيد وأثره في اختلاف الفقياء يشمل زيادة الثقة والشاذ والمضطرب وغير ذلك. وأمّا الثالث فخصصت بالحديث عن قواعد وق ا رئن الترجيح عند اختلاف الأسانيد وتشمل أنواع الق ا رئن. Abstract in English Touched on in this research different grounds the Hadith and its impact on different jurists , Vartoat in my research is divided into three chapters dealt with in the first chapter to clarify the reasons for the difference in the grounds , which is the illusion and error and the behavior of the serious and the heart and the insertion and others. The second , I talked about the difference in the grounds and its impact on different jurists includes increasing confidence and abnormal turbulent and so on. The third Fajsst talking about the rules of evidence and penalties at different grounds and include the types of clues.
مذكرة